Skill Mismatch and the Costs of Job Displacement - Frank Neffke; Ljubica Nedelkoska; Simon Wiederhold (Center for Economic Studies and ifo Institute (CESifo), 2022)
When workers are displaced from their jobs in mass layoffs or firm closures, they experience lasting adverse labor market consequences. We study how these consequences vary with the amount of skill mismatch that workers experience when returning to the labor market. Using novel measures of skill redundancy and skill shortage, we analyze individuals' work histories in Germany between 1975 and 2010. We estimate difference-in-differences models, using a sample in which we match displaced workers to statistically similar non-displaced workers. We find that displacements increase the probability of occupational change eleven fold, and that the type of skill mismatch after displacement is strongly associated with the magnitude of post-displacement earnings losses. Whereas skill shortages are associated with relatively quick returns to the counterfactual earnings trajectories that displaced workers would have experienced absent displacement, skill redundancy sets displaced workers on paths with permanently lower earnings.
Keywords: 330